Anisotropic spline approximation with non-uniform B-splines. Issue 2 (25th January 2018) - Sissouno, N.
Abstract : Recently the author and U. Reif introduced the concept of diversification of uniform tensor product B-splines. Based on this concept, we give a new constructive modification of non-uniform B-splines. The resulting spline spaces are perfectly fitted for the approximation of functions defined on domains . We build a bounded quasi-interpolant and prove that for our spline spaces an anisotropic error estimate in the -norm, , is valid. In particular, we show that the constant of the error estimate does not depend on the shape of or the knot grid.